The "Athlete Killer" hidden in the internet: The impact of cyber-violence on high-level athletes` perceived performance - Lu, Y.; Xu, H.; Xie, B.; Jiang, Y.; Zhang, Y.; Fan, T.; Zhou, W. (International Journal of Sport Psychology, 2024)
This study, involving 245 high-level athletes who have suffered from cyber-violence, explores the factors affecting their perceived competition performance. It aims to provide suggestions and ideas for the prevention and management of cyber-violence against athletes. The analysis using Structural Equation Modeling (SEM) shows that cyber-violence significantly impacts high-level athletes` depressive mood and perceived competition performance. Depressive mood plays a significant mediating role between cyber-violence and perceived competition performance. The analysis using fuzzy-set Qualitative Comparative Analysis (fsQCA) reveals a diverse set of conditions affecting athletes` perceived competition performance. The study finds that, apart from cyber-violence and depressive mood, demographic char- acteristics such as gender and age are also important factors. The study discusses relevant literature and offers substantial suggestions for managing cyber-violence.